Regulation of Utility Valuation in Pennsylvania (Book). - Thompson, C. Woody; Winter, Sidney G. (The Accounting Review, 1943)
Abstract Reviews the book "Regulation of Utility Valuation in Pennsylvania," by William Roy Buckwalter.